If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -5 = 7y + -41 Reorder the terms: -5 + 11y = 7y + -41 Reorder the terms: -5 + 11y = -41 + 7y Solving -5 + 11y = -41 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -5 + 11y + -7y = -41 + 7y + -7y Combine like terms: 11y + -7y = 4y -5 + 4y = -41 + 7y + -7y Combine like terms: 7y + -7y = 0 -5 + 4y = -41 + 0 -5 + 4y = -41 Add '5' to each side of the equation. -5 + 5 + 4y = -41 + 5 Combine like terms: -5 + 5 = 0 0 + 4y = -41 + 5 4y = -41 + 5 Combine like terms: -41 + 5 = -36 4y = -36 Divide each side by '4'. y = -9 Simplifying y = -9
| 11x-145=5x-13 | | 6n-4(n+3)=34 | | 84=2(35)+2w | | 50-4x=5x+17 | | 7=x(3+10x)-6x | | 1.4+1=10 | | -6=b+18 | | 2.25(4x+-4)=2+10x+12 | | 9a+4a-6b-4a= | | 16+10=3x+5-2x+6x | | 350+25d=67d+25d | | 2.25(4x-4)=2+10+12 | | 6=x-8 | | -12(k-1)=-(3k-6) | | 9w+10w-8w= | | 2x+8-7x=48 | | 7z-5z-4z= | | 20+20+3g+2g=115 | | x(2)=-121 | | 2x+3=19-3x | | 2b+4b+5b= | | 8+3x+2x=23 | | 5(x-4)+2(x+1)=3(2-4) | | 14-2q-5=-2q+9 | | -8v-4v= | | -3*-5=51 | | 8g-2g= | | p=45-q | | 9q+(-4q)= | | 92=4+6w+2w | | 7w+4w= | | 8p+(-6p)+6m= |